PENAKSIR RASIO PROPORSI YANG EFISIEN UNTUK RATA-RATA POPULASI PADA SAMPLING ACAK BERSTRATA - Devri Maulana; Arisman Adnan; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article we review three proportion ratio estimators for the population mean on stratified random sampling, i.e. traditional proportion ratio estimator, proportion ratio estimator  using coefficient of regression, and proportion ratio estimator  usingcoefficient of regression and curtosis as discussed by Singh and Audu [5]. The three estimators  are  biased  estimators,  then  the  mean  square  error  of  each  estimator  is determined.  Furthermore, these mean square errors are compared to each other. This comparison shows that the proportion ratio estimator using coefficient of regression and curtosis more efficient than other estimators.